Viewing ultrasound images in the abortion clinic: clients' and health care professionals' opinions. (4th March 2019) - Simpson, J. D.; Brown, A.
Abstract: Objectives: The U.K guidance recommends that health care professionals (HCPs) offer clients the opportunity to view their pre-abortion ultrasound scan. As the U.K research on this topic is limited, our objectives were to assess current practice and local population needs, through a prospective, observational survey, to improve the quality of abortion care delivery. Methods: Over a 4 month period all clients attending the Sandyford Termination of Pregnancy and Referral (TOPAR) unit for abortion assessment were asked to fill in an anonymous questionnaire. A further questionnaire was distributed to HCPs working in the TOPAR unit. Results: A total of 406 questionnaires were analysed. Almost half ( n = 194; 47.8%) of respondents had been offered the opportunity to view their ultrasound scan, of whom 31.4% (61/194) had accepted. The majority of those who had accepted ( n = 48; 78.7%) concluded that they were more likely to proceed with the abortion or that viewing the scan had made no difference to their decision to proceed. All HCPs ( n = 18; 100%) completed the questionnaire, 55.6% ( n = 10) of whom responded that they routinely offered viewing. Ultrasound was not routinely offered by 25% ( n = 3) and 83.3% ( n = 5) of medical and nursing staff, respectively. Conclusions: We found inconsistent practice within our unit. Despite HCPs building rapport with clients prior to the ultrasound, not all clients who wished to have the opportunity to view their scan were identified. It is evident that many clients wish to have the option to choose for themselves whether they want to view their ultrasound scan, rather than be judged by an HCP as someone who might benefit from it.